2011
DOI: 10.1371/journal.pone.0023530
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Syndecan-1 Shedding after Hemorrhagic Shock and Resuscitation

Abstract: The early use of fresh frozen plasma as a resuscitative agent after hemorrhagic shock has been associated with improved survival, but the mechanism of protection is unknown. Hemorrhagic shock causes endothelial cell dysfunction and we hypothesized that fresh frozen plasma would restore endothelial integrity and reduce syndecan-1 shedding after hemorrhagic shock. A prospective, observational study in severely injured patients in hemorrhagic shock demonstrated significantly elevated levels of syndecan-1 (554±93 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
185
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(198 citation statements)
references
References 43 publications
9
185
0
4
Order By: Relevance
“…In our protocol, complete glycocalyx restoration occurred following infusion of smaller plasma volumes than previously reported (32). The data support the concept of vascular stabilization by infused plasma (23), in which glycocalyx recovery is an important component. The early use of FFP as a resuscitative agent has been associated with improved survival after hemorrhagic shock (11,28,31).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our protocol, complete glycocalyx restoration occurred following infusion of smaller plasma volumes than previously reported (32). The data support the concept of vascular stabilization by infused plasma (23), in which glycocalyx recovery is an important component. The early use of FFP as a resuscitative agent has been associated with improved survival after hemorrhagic shock (11,28,31).…”
Section: Discussionsupporting
confidence: 85%
“…The disruption of endothelial integrity by hemorrhagic shock leading to syndecan-1 shedding, observed in this work, has been reported previously (23). Measurements of glycocalyx thickness in syndecan-1-deficient mice suggest that the lack of syndecan-1 may be compensated by the increase in expression of other proteoglycans.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Haywood-Watson et al found elevated plasma syndecan-1 concentration in severely injured trauma patients in hemorrhagic shock. 39 They also found that 3 proinflammatory cytokines, IFN-␥, IL-1␤, and fractalkine, were negatively associated with plasma syndecan-1 levels, presumably by their binding and activation of endothelium. These investigators then showed that endothelial barrier function was reduced in association with shedding of syndecan-1 and that this process was inhibited by application of fresh frozen plasma in vitro.…”
Section: Combining Injury and Shock To Produce Ticmentioning
confidence: 95%
“…Our hemorrhage also differs from clinical practice in which a state of systemic inflammation with increased microvascular permeability, tissue damage and prolonged hypovolemia often exist. FFP may counteract glycocalyx sheeding and permeability increases following hemorrhage indicate that the volume expanding properties of FFP may depend on the prevailing pathophysiology [19,20].…”
Section: Discussionmentioning
confidence: 99%